Optimizing The Topological Working of Modern Transportation Systems in Smart Cities Using Mobius Strips - Souumya Kothari (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Contemporary urban mobility networks are progressively strained by congestion, inefficient land use, and rigid infrastructure. With smart cities aspiring to adaptive and sustainable mobility, new design paradigms are crucial. This study proposes a topological framework drawn from the Möbius strip—a non-orientable surface with a single-sided continuous geometry—to reconsider transportation networks. Capitalizing on the special characteristics of the Möbius strip, the research formulates a model of continuous flow to eradicate intersections, U-turns, and bidirectional lane splits. A graph-theoretical model and SUMO-based simulations are utilized to devise and assess a Möbius-integrated transportation system. Comparative results relative to traditional systems demonstrate a dramatic improvement: a 28.6% decrease in travel time, 38.6% reduction in congestion, 27.8% increased vehicle throughput, and 38.1% improved lane capacity. Moreover, up to 18% energy consumption is minimized. All these outcomes prove that Möbius-inspired topologies have the potential to transform urban transport planning by maximizing fluidity, space, and sustainability—providing a promising, mathematically sound solution for smart cities of the future.